2014
DOI: 10.4236/ojd.2014.34019
|View full text |Cite
|
Sign up to set email alerts
|

Social Connectedness Predicts Lower Loneliness and Depressive Symptoms over Time in Adolescents

Abstract: Although research has shown that loneliness in adolescents leads to higher rates of depressive symptoms, the presumed protective factor of social connectedness has not been studied in conjunction with these two constructs. The aim of the present study was to determine if social connectedness would predict lower loneliness and depressive symptoms over time in a large sample of adolescents. A large sample of adolescents (N = 1774; 9 -16 years at Time 1) were surveyed three times, separated by one year each, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 37 publications
4
40
0
Order By: Relevance
“…The results are also consistent with the Social Cure perspective (Jetten et al, 2012). The present study replicates the previously established negative relationship between group identification and loneliness (e.g., Haslam et al, 2016;Jose & Lim, 2014) and between group identification and depression (e.g., Cruwys et al, 2014), but extends this by showing evidence of serial mediation between these variables: Family identification is a negative predictor of loneliness, which is in turn a positive predictor of depression. Moreover, the model presented in the present study further extends the Social Cure literature by showing that, in turn, depression is a positive predictor of poor sleep quality/ insomnia severity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results are also consistent with the Social Cure perspective (Jetten et al, 2012). The present study replicates the previously established negative relationship between group identification and loneliness (e.g., Haslam et al, 2016;Jose & Lim, 2014) and between group identification and depression (e.g., Cruwys et al, 2014), but extends this by showing evidence of serial mediation between these variables: Family identification is a negative predictor of loneliness, which is in turn a positive predictor of depression. Moreover, the model presented in the present study further extends the Social Cure literature by showing that, in turn, depression is a positive predictor of poor sleep quality/ insomnia severity.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, in their investigation of the efficacy of the Social Cure-inspired Groups4Health intervention, Haslam, Cruwys, Halsam, Dingle, and Xue-Ling Chang (2016) showed that reductions in loneliness were driven by participants' increased identification with their Groups4Health support group. Additionally, Jose and Lim (2014) showed a negative relationship between group identification and loneliness over time in an adolescent sample.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Specifically, we are interested in the construct of connectedness. Connectedness has been observed to promote resilience in adolescents and has been associated with positive mental, physical, psychological and educational outcomes (Abubakar, van de vijver, Mazrui, Murugami, & Arasa, 2014;Dang, 2014;Jose & Lim, 2014). Among adolescents from highly marginalized community such as Roma, connectedness may be a salient source of resilience since it moderates the impact of exposure to adverse conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The micro-system is made up of salient relationships such as parents, siblings, teachers and peers, whereas the macro-system is made up of institutions in the youth's life that he or she experiences on a day-to-day basis, such as family, school, and once neighborhood (Karcher et al, 2008). Social connectedness among adolescents has been linked to a host of youth outcomes including reduced problem behaviors, and better mental health outcomes (Abubakar et al, 2014;Crespo, Kielpikowski, Jose, & pryor, 2010;Jose & Lim, 2014). oberle, Schonert-Reichl, and Zumbo (2011) observed that ecological assets (i.e., school connectedness, perceived neighbourhood support, parental and positive peer relationship) significantly and positively predicted early adolescents' life satisfaction.…”
Section: Introductionmentioning
confidence: 99%